Geographic variations in opioid overdose patterns in Pennsylvania during the COVID-19 pandemic. (January 2023) - King, Brian; Holmes, Louisa M.; Rishworth, Andrea; Patel, Ruchi
Abstract: The convergence of the opioid epidemic and the COVID-19 pandemic has created new health challenges throughout the United States. Since the onset of the pandemic, media attention and scholarly research have drawn attention to the intersections of addiction and COVID-19. However, there remain few empirical studies that examine the direct impacts of the COVID-19 pandemic for opioid overdose patterns. Even fewer have integrated quantitative and qualitative methods to detail the place-specific dynamics shaping opioid overdose and addiction treatment during the COVID-19 pandemic. This article measures and maps change in the age-adjusted rate of opioid-related overdose incidents at the county level from 2018 to 2020. These analyses are combined with interviews conducted since December 2020 with public health providers in the state of Pennsylvania to identify the key factors influencing opioid misuse and transformations in addiction treatment practices. Highlights: The US opioid epidemic and the COVID-19 pandemic have created new health challenges. We analyze change in the age-adjusted rate of overdose incidents from 2018 to 2020. These incidents are mapped at the county level in the state of Pennsylvania. Interviews reveal place-based factors shaping the confluence of COVID-19 and opioid misuse.